2015
DOI: 10.1007/s00405-015-3543-7
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminolysis and carcinogenesis of oral squamous cell carcinoma

Abstract: Glutaminolysis is a crucial factor for tumor metabolism in the carcinogenesis of several tumors but has not been clarified for oral squamous cell carcinoma (OSCC) yet. Expression of glutaminolysis-related solute carrier family 1, member 5 (SLC1A5)/neutral amino acid transporter (ASCT2), glutaminase (GLS), and glutamate dehydrogenase (GLDH) was analyzed in normal oral mucosa (n = 5), oral precursor lesions (simple hyperplasia, n = 11; squamous intraepithelial neoplasia, SIN I-III, n = 35), and OSCC specimen (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…It has been postulated that several pathways of carcinogenesis are associated with metabolic phases of transformation in tumor cells, which can be regarded as an integrated metabolic ecosystem [1,3,4]. Our recent studies in OSCCs demonstrated glycolysis, glutaminolysis, and mitochondrial oxidative phosphorylation (OXPHOS) to play major roles in tumor metabolism [1,[4][5][6]. Moreover, the pentose phosphate pathway (PPP) [7] is a crucial factor for survival of OSCC tumor cells [8,9].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been postulated that several pathways of carcinogenesis are associated with metabolic phases of transformation in tumor cells, which can be regarded as an integrated metabolic ecosystem [1,3,4]. Our recent studies in OSCCs demonstrated glycolysis, glutaminolysis, and mitochondrial oxidative phosphorylation (OXPHOS) to play major roles in tumor metabolism [1,[4][5][6]. Moreover, the pentose phosphate pathway (PPP) [7] is a crucial factor for survival of OSCC tumor cells [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…Our recent studies [1,4] demonstrated glycolysis, mitochondrial OXPHOS, and glutaminolysis as important cancer metabolism pathways for oral carcinogenesis. However, analysis of thiamine-dependent enzymes within the network of these pathways as indication for 'metabolic therapies' [22] in OSCC has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Dependent on NADPH/H+, polyunsaturated fatty acid metabolism, and the mevalonate and glutaminolysis, metabolic pathways have been implicated in ferroptosis. [27][28][29][30][31] Meanwhile, exploitation of ferroptosis in response to specific compounds is also attracting strategy in cancer therapy. Our study primarily showed the GPX4 overexpression did not inhibit ferroptotic cell death induced by RSL3 and low-concentration PTX.…”
Section: Discussionmentioning
confidence: 99%
“…previously demonstrated that HER2-type breast cancer expresses the highest SLC1A5 levels evaluated to date using immunohistochemistry. SLC1A5 expression is also associated with non-small cell lung cancer [10], lacrimal gland adenoid cystic carcinoma [11], oral squamous cell carcinoma [12], pancreatic ductal carcinoma [13], tongue cancer [14], and colorectal cancer [15]. Notably, while recent research has shown that SLC1A5 expression is increased in esophageal carcinoma [16], the biological significance of SLC1A5 in the development and/or progression of esophageal cancer has not been reported.…”
Section: Introductionmentioning
confidence: 99%